(untitled) (Cahiers Africains de rhétorique, 2025)
Power, in all its forms, has always arused enthousiasm, but also crystallized passions. An expression of authority and exemplarity, it is intimately linked to divine power, with reference to pharaohs and deities in many civilizations in Africa and the rest of the world. However, it is increasinggly controversial. Certainly, its ability to mobilize around common causes and to resolve civil and land disputes and family conflicts is no longer in question, but the exercise of political aspect seems not suited to the current modern context and the aspirations of societies in full change : non-inclusive, implacable decisions, male dominance, mystery and esoterism. This is ambivalent image is one reflected by literature, in this case Burkinabe literature. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back